TAHFIDZ AL-QUR’AN DENGAN METODE BIL-QOLAM DI MADRASAH TSANAWIYAH (ISLAMIC BOARDING SCHOOL) AL- AZHARY AJIBARANG BANYUMAS - Rohmad, Rohmad; Muslimin, Muslimin (MAGHZA, 2017)
The problems studied in this research are (1) How to study tahfidz Al-Qur'an with method of Bil-Qolam in Madrasah Tsanawiyah (Islamic Boarding School) Al-Azhary  Ajibarang Banyumas year 2016/2017 ?; (2) How is the learning result of tahfidz Al-Qur'an with  the method of Bil-Qolam in Islamic Boarding School Al-Azhary Ajibarang Banyumas year 2016/2017 ?. This study aims to describe and analyze the process and learning outcomes of tahfidz Al-Qur'an with the method of Bil-Qolam in Madrasah Tsanawiyah (Islamic Boarding School) Al-Azhary Ajibarang Banyumas year 2016/2017? The result of the research shows that learning of Qur'anic tahfidz with the method of Bil-Qolam in Islamic Boarding School Al- Azhary Ajibarang Banyumas year 2016/2017 is applied by using morning and afternoon  learning system, and learning is done with 4 activities opening for 5 minutes, talqin and Ittiba' activities for 5 minutes, urdhoh for 20 minutes, and urdhoh or individual drill for 30 minutes. Whereas the learning outcomes for each year always reach the targets determined by the madrasah (school) supported by the spirit and students' curiosity, the methods used, and programs that are run intensively.